2020
DOI: 10.1371/journal.pbio.3000940
|View full text |Cite
|
Sign up to set email alerts
|

Gradient in cytoplasmic pressure in germline cells controls overlying epithelial cell morphogenesis

Abstract: It is unknown how growth in one tissue impacts morphogenesis in a neighboring tissue. To address this, we used the Drosophila ovarian follicle, in which a cluster of 15 nurse cells and a posteriorly located oocyte are surrounded by a layer of epithelial cells. It is known that as the nurse cells grow, the overlying epithelial cells flatten in a wave that begins in the anterior. Here, we demonstrate that an anterior to posterior gradient of decreasing cytoplasmic pressure is present across the nurse cells and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 102 publications
3
25
1
Order By: Relevance
“…To test and challenge this aspect, it could be interesting to artificially merge two or more embryos before blastulation to see if several, uncoupled, cavities may form. Beyond lumenogenesis, we expect our theory to be relevant for describing the hydraulic cell coarsening phenomena underlying Drosophila and C. elegans oogenesis Alsous et al ( 2021 ); Lamiré et al ( 2020 ); Chartier et al ( 2020 ). As we showed earlier Dumortier et al ( 2019 ), gradients of cell mechanical properties can be sufficient to spatially bias lumen coarsening, and this mechanism is the main symmetry breaking process put forward to explain cell competition in oogenesis as well.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…To test and challenge this aspect, it could be interesting to artificially merge two or more embryos before blastulation to see if several, uncoupled, cavities may form. Beyond lumenogenesis, we expect our theory to be relevant for describing the hydraulic cell coarsening phenomena underlying Drosophila and C. elegans oogenesis Alsous et al ( 2021 ); Lamiré et al ( 2020 ); Chartier et al ( 2020 ). As we showed earlier Dumortier et al ( 2019 ), gradients of cell mechanical properties can be sufficient to spatially bias lumen coarsening, and this mechanism is the main symmetry breaking process put forward to explain cell competition in oogenesis as well.…”
Section: Discussionmentioning
confidence: 61%
“…Here, we have shown that active ion pumping may be an additional source of spatial bias for coarsening. Active osmotic volume control emerges hence as a novel mode of symmetry breaking for tissue patterning, that could be relevant also to oogenesis Alsous et al ( 2021 ); Lamiré et al ( 2020 ); Chartier et al ( 2020 ), liquid phase transition of biological condensates Jalihal et al ( 2021 ) and plant tissue growth Cheddadi et al ( 2019 ); Long et al ( 2020 ). Active ion pumping can also largely affect the collective lumen dynamics, with the emergence of a novel coarsening regime dominated by coalescence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations